METHODS TO INCREASE THE COMPETITIVENESS IN INDUSTRY - Ion STANCU; Adriana LAZARESCU (Management & Marketing)
Industrial firms are different between them for their economicalcharacteristics, competitive situations and their prospects. Industry andcompetitive analysis use a lot of concepts and methods for obtaining a clearimage concerning the variable conditions from industry and competitivestrong forces. Economical characteristics of industry are important for theirstrategic implications.